Slab Induced Mantle Upwelling Beneath the Anatolian Plateau. Issue 11 (7th June 2022) - Lynner, Colton; Delph, Jonathan R.; Portner, Daniel E.; Beck, Susan L.; Sandvol, Eric; Özacar, A. Arda
Abstract: The subducting African Plate in the easternmost Mediterranean is actively tearing and deforming beneath the Anatolian Plate as the margin transitions from long‐lived subduction to collision. In central Anatolia, the subducting slab is characterized by both lateral and vertical slab tears. We investigate patterns of mantle flow around the edges of a contorting and fragmenting African slab segment, called the Cyprean slab, using measurements of shear wave splitting. We observe three distinct regions of coherent shear wave splitting that correlate with the segmentation boundaries of the Cyprean slab. Regionally coherent mantle flow occurs near both the eastern and western the edges of the slab. These regions of coherent splitting are separated by an area of null splitting that encompasses the Central Anatolian Volcanic Province near the easternmost edge of the slab. The null measurements likely result from mantle upwelling due to the displacement of asthenosphere from the vertical Cyprean slab. Plain Language Summary: The subducting African Plate in the easternmost Mediterranean has been tearing beneath central Turkey as the region switches from subduction to collision. This area provides one of the best chances to study how tearing of a subducting plate impacts patterns of mantle flow during the last stages of subduction. We study mantle flow around the edges of the fragmented Cyprean slab using measurements of shear wave splitting, which provide information on the direction of mantle flow via the fast splitting direction and delay time. We see three distinct regions of mantle dynamics that relate to the boundaries of the Cyprean slab. We observe coherent flow near both the eastern and western edges of the slab that align with background regional dynamics. The two regions with coherent flow are separated by an area of anomalously absent splitting. This likely indicates that mantle is flowing upward next to the vertical Cyprean slab segment in central Anatolia, including just below the Central Anatolian Volcanic Province. Key Points: Shear wave splitting in central Anatolia shows evidence of mantle upwelling around the Cyprean slab Weak toroidal return flow exists along the western edge of the Cyprean slab and not along the eastern boundary Background mantle flow driving the Anatolian Plate is seen at many Continental Dynamics: Central Anatolian Tectonics stations